Desenvolvimento sustentável e gestão socioambiental empresarial: uma abordagem crítica sobre as concepções, políticas e práticas de sustentabilidade no mundo corporativo - Soares, Ana Paula Fleury de Macedo (2016)
The objective of this thesis is critical analysis of the relationship between the conceptions and policies that underlie the strategies and practices of Sustainable Development and Corporate Social and Environmental Management. Discussions about the performance of companies in society occupy a large part of the public debate agenda, mainly regarding their ability to design guidelines that contribute to economic growth capable of balancing economic, environmental and social development. Literature is divided reflecting two different approaches: the first one, which may be called the dominant or mainstream, focuses on the ability of companies to provide solutions to problems related to sustainable development. It assumes a principle that there is a progressive evolution of Corporate Social Environmental Management, and that the more developed companies are in their stages, the deeper sustainability is rooted within them. In this way, this thinking proposes a series of steps to be followed by companies so that they reach a level of excellence. This literature is normative and technical, and does not address conflicts and contradictions in this trajectory. The second approach found in literature may be called the critical one. It points out the existence of paradoxes, contradictions and conflicts among stakeholders, their positions and needs, indicating that Sustainable Development and Corporate Social and Environmental Management can not be discussed without taking into account these divergences and the need for trade off. The thesis consists in the identification of the issues that normative thinking does not address, and that can be considered gaps in the reflections on Sustainable Development and Corporate Social and Environmental Management. These issues were systematized in categories, and analyzed through in-depth interviews. As a result, the driver of sustainability is the pursuit of economic performance, and environmental and social aspects can be considered sub-items of this topic. In the context of sustainability, the relations between company and society are shaped by the market, and the companies have ascendancy in the dynamics of social life. Finally, considering that the contemporary mode of production is organized in supply chains, often 'co-ordinated' by the corporations, the larger their size, the greater their negotiating power in relation to surrounding communities, suppliers, or even to the State.